Supervivencia de larvas de Ranitomeya reticulata Boulenger, 1883 y R. amazonica Schulte, 1999 (Anura: Dendrobatidae) en cultivo ex situ en bosque de varillal alto seco, Loreto - Perú - Ruiz Cerrón, Abraham Jefferson Jesús (2022)
Since July to November 2019 we study the survival of larvae on Ranitomeya reticulata and R. amazonica in culture ex situ in whiteland forest (Loreto–Perú), by the uss of plastic cups with wáter and detritus. The results show that the STD of water various between 0.03 and 0.053 ppt, the electric conductivity was 0.059 and 0.124 mS/cm (milisiemens), pH between 6.616 and 4.988 (acid pH) disolved oxygen 0.4 ppm and Nitritos 0.038 and 0.046. The mínimum temperatura was 24.3°C and máximum 29.2 °C with average ± 26.00 °C (D.E. = 1.7152). The larvae of Ranitomeya amazonica and R. reticulata has a survival of 85 y 90 % respectively. We concluded that the survival of the larvae of Ranitomeya reticulata and R. amazonica in culture ex situ, during his metamorphosis it was high.